Strategy for Improving the Quality of Islamic Higher Education Management in the Independent Curriculum Era - Arifin, Zainul; Hepni, Hepni; Anwar, Moh. (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
This research examines strategies for improving the quality of Islamic higher education management in the Independent Curriculum Era. This research uses a qualitative research library-type method, conducting an in-depth study related to the Strategy for Improving the Quality of Islamic Higher Education Management in the Independent Curriculum Era with data and data sources obtained from books and national and international journal articles related to the keywords Strategy, Improving the Quality of Management, Islamic Higher Education, Independent Curriculum. The research results on strategies to improve the quality of Islamic higher education management in the Independent Curriculum era require a holistic and innovative approach to ensure educational institutions can maintain standards of excellence and relevance in facing changes in globalization. Some strategies that can be implemented to improve the quality of Islamic higher education management in the Independent Curriculum era include quality leadership, namely leadership that is visionary and innovation-oriented. Improving Curriculum and Learning, the curriculum must be structured to integrate Islamic values ​​with the latest science and technology. The application of information and communication technology allows educational institutions to increase operational efficiency learning flexibility, and be responsive to student needs. Development of human resources according to the demands of the times, as well as collaboration with various external parties by expanding networks, for example collaborating with other universities to create quality education programs.